2021
DOI: 10.1177/15248380211030243
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Slaughterhouse Employment: A Systematic Literature Review

Abstract: The role of a slaughterhouse worker (SHW) involves the authorized killing of living beings, yet there is limited understanding of the consequences this behavior has on their well-being. The purpose of this systematic review is to collate and evaluate the current literature on the psychological impact of slaughterhouse employment. Fourteen studies met the specific a priori inclusion criteria. The findings from this review were demarcated by the focus of studies: (1) the prevalence of mental health disorders, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For example, many forms of drug use are criminalized, and once a person enters the criminal legal system and obtains a criminal record their job opportunities decrease. Persons with a criminal record disproportionately enter low-paid jobs that can be seen as dehumanizing (Slade & Alleyne, 2021). Drug use stigma is a means to socially and economically disadvantaged people and groups who do not conform.…”
Section: Drug Usementioning
confidence: 99%
“…For example, many forms of drug use are criminalized, and once a person enters the criminal legal system and obtains a criminal record their job opportunities decrease. Persons with a criminal record disproportionately enter low-paid jobs that can be seen as dehumanizing (Slade & Alleyne, 2021). Drug use stigma is a means to socially and economically disadvantaged people and groups who do not conform.…”
Section: Drug Usementioning
confidence: 99%
“…Job dissatisfaction in workers <30 years of age has been widely reported because workers have experienced workplace violence by co-workers or have worked in a violent environment (Brown, Myers, Casteel, & Rauscher, 2020). Reeve, Rogelberg, Spitzmüller, and DiGiacomo (2005), found that animal shelter employees who were directly involved in euthanasia had significantly higher levels of job stress, stress-related somatic complaints, and lower levels of job satisfaction than did animal shelter employees who were not involved in euthanasia, which suggests that animal slaughter might be an important cause of work-related stress (Slade & Alleyne, 2022).…”
Section: Profiles Of Animal Welfare Ambiguous Workersmentioning
confidence: 99%
“…Slaughterhouse work is characterized by high staff turnover, absenteeism, disciplinary measures, demanding schedules, and exposure to death on a daily basis, which can exert psychological pressure that can lead to occupational stress, burnout, and post-traumatic stress syndrome (Emhan, Yildiz, Bez, & Kingir, 2012;Victor & Barnard, 2016). Those conditions can cause anxiety, irritability, sadness, tiredness, disinterest, lethargy, and violence-supportive attitudes (Slade & Alleyne, 2022). Those circumstances can arouse in workers' negative attitudes toward animals, which can affect the human-animal relationship and lead to marked stress in the animals (Hemsworth, Barnett, Coleman, & Hansen, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Yoked by capital' (Beldo, 2017, p. 119) the body of Gallus gallus thus creates surplus energy (and hence value) in the form of extra muscle. Such surpluses come with substantial impacts on the bodies of human labour charged with the 'authorised killing' of animals (Slade & Alleyne, 2021) and managing their transformation into commodities and meat. These include acute and chronic psychological and physiological injuries.…”
Section: Embodied Surplus and Displacementmentioning
confidence: 99%